Freedom of Expression in the US Constitution: Formation and Development (Law and Safety, 2019)
The essence of such rights as the right to freedom of expression and the right to freedom of speech has been analyzed. Based on the United States regulations, the author has compared approaches to understanding and interpreting freedom of speech and freedom of expression.Freedom of expression has been studied as one of the dominant values of constitutionalism, a precondition for democracy and the rule of law. Historical aspects of the formulation of the right to freedom of speech in the United States of America, as well as its consistent regulatory enshrinement and interpretation have been analyzed. Different approaches to the constitutional proclamation of the freedom of speech have been researched and the optimal formulation of the said law has been clarified. Particular attention has been paid to the differences between American and European concepts of freedom of expression, and fundamentally different points in its understanding.The importance of banning the oppression of freedom of expression for the development of a democratic society and the market for ideas has been substantiated.Particular attention has been paid to the study of the formation and development of these rights under US law and their enactment. Based on a comparison of American and Ukrainian options for guaranteeing this right, their advantages and disadvantages have been highlighted, which may assist in gaining positive experience for Ukraine.The author has made conclusions regarding the higher level of guaranteeing the right to freedom of expression and freedom of speech in the practice of the United States, although these rights are more detail enshrined in Ukrainian law.The author has argued in favor of the fact that Ukraine should take into account the American approach to the protection of the right to freedom of expression and freedom of speech, as well as to establish a mechanism for their observance as fundamental personal human and civil rights.
Keywords: freedom of expression; freedom of thought; freedom of speech; freedom of the press; rights and freedoms of a man and citizen; American constitutionalism; restriction of freedom of expression